Bifunctional Carbon Dots Derived From an Anaerobic Bacterium of Porphyromonas gingivalis for Selective Detection of Fe3+ and Bioimaging. (21st December 2020) - Liu, Lijuan; Qin, Kunhao; Yin, Shuang; Zheng, Xiaodan; Li, Hongmei; Yan, Hui; Song, Pengfei; Ji, Xiuling; Zhang, Qi; Wei, Yunlin; Zhao, Limin
Abstract: In this study, for the first time, Porphyromonas gingivalis, an anaerobic bacterium, was selected to synthesize carbon dots. The achieved P. gingivalis –carbon dots (Pg‐CDs) exhibited strong fluorescence and high stability with capability for dual function as Fe 3+ sensor and intracellular imaging agent. The detection limit for Fe 3+ was as low as 1.85 µm . On the other hand, the prepared Pg‐CDs were an excellent candidate for biosensor with high biocompatibility. Abstract : In this work, carbon dots with high stability were synthesized from Porphyromonas gingivalis, an anaerobic bacterium. The achieved CDs held promising potential both in Fe 3+ detection and intracellular imaging owning to their strong fluorescence and nontoxicity.